Development of an Educational Game Based on Picture Quiz as an Interactive Learning Medium - Eldo, Handry; Najmi, Muazziss (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
Educational games play a vital role in improving cognitive abilities and creativity in children and adults. This study discusses the development of a picture-based quiz game that integrates interactive learning elements with engaging visual challenges. The game, titled